Possibilities of reinforcement of subtle translucent concrete panel - Věra Kabíčková; Jakub Hájek; Tomáš Vlach; Jakub Řepka (Acta Polytechnica CTU Proceedings, 2024)
Textile-reinforced concrete not only has many advantages that lead to less consumption of primary resources, but also enables the creation of thin and subtle elements. The high performance of such elements allows us to create interesting architectural features, such as translucent concrete. This article focusses on the possibility of reinforcing translucent concrete panels.